Upholding civility towards diversity in urban public space: exploring the makings of conviviality and belonging in Cape Town's city centre - Adoné, Kitching (Social Anthropology, 2016)
This study is concerned with the makings of conviviality in the market spaces in Cape Town's city centre. It investigates the strategies through which diverse actors in the Church Street Antique Market, Greenmarket Square and St George's Mall negotiate - even celebrate - difference. In doing so the study offers an ethnographic account of everyday life in the market spaces, and considers the ways in which prosaic actions and interactions contribute to the cultivation of habits of accommodation. The study shows that conviviality emerges out of everyday negotiations of space, where actors recognise their shared interest in securing livelihoods. Furthermore, it argues that conviviality is not only rooted in the recognition of a basic sameness, but also in the acknowledgement that interconnections with diverse others are necessary for the achievement of individual and collective goals. Finally, this work brings attention to the significance of habits of accommodation for experiences of belonging and citizenship.